2021
DOI: 10.3390/ijms22105370
|View full text |Cite
|
Sign up to set email alerts
|

Tau Exon 10 Inclusion by PrPC through Downregulating GSK3β Activity

Abstract: Tau protein is largely responsible for tauopathies, including Alzheimer’s disease (AD), where it accumulates in the brain as insoluble aggregates. Tau mRNA is regulated by alternative splicing, and inclusion or exclusion of exon 10 gives rise to the 3R and 4R isoforms respectively, whose balance is physiologically regulated. In this sense, one of the several factors that regulate alternative splicing of tau is GSK3β, whose activity is inhibited by the cellular prion protein (PrPC), which has different physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 105 publications
(140 reference statements)
0
4
0
Order By: Relevance
“…Relevantly our data demonstrate a decrease of ptau in the absence of Aβ deposits, similarly, as happens in the above-cited manuscript with Aβ presence. Although differences in genes affected by the absence of PrP C have been described in several manuscripts with differences in the genetic background (i.e, [14, 28, 103], we previously reported that ZH3 Prnp 0/0 mice showed decreased levels of tau and increased 3R/4Rtau ratio vs wild-type mice [82]. In addition, changes in ptau and levels of tau were described during the development of FVB/N Prnp 0/0 mice vs wild-type [14].…”
Section: Discussionmentioning
confidence: 99%
“…Relevantly our data demonstrate a decrease of ptau in the absence of Aβ deposits, similarly, as happens in the above-cited manuscript with Aβ presence. Although differences in genes affected by the absence of PrP C have been described in several manuscripts with differences in the genetic background (i.e, [14, 28, 103], we previously reported that ZH3 Prnp 0/0 mice showed decreased levels of tau and increased 3R/4Rtau ratio vs wild-type mice [82]. In addition, changes in ptau and levels of tau were described during the development of FVB/N Prnp 0/0 mice vs wild-type [14].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we investigated two main issues concerning the role of miR-519a-3p in AD. On the one hand, there is its possible involvement in reducing PrP C expression levels in the evolution of the disease (Vergara, Ordonez-Gutierrez et al 2015; Lidon, Llao-Hierro et al 2021). In fact, the role of PrP C in AD and other NDDs is still a matter of debate, as some argue for its neuroprotective function while others point to it as an enhancer of the neurotoxicity associated with NDD (discussed in (Gavin, Lidon et al 2020)).…”
Section: Discussionmentioning
confidence: 99%
“…Prion protein PrPC serves as an upstream regulator that inhibits GSK3β activation. 176 Furthermore, interferon‐gamma (IFN‐γ) initiates cellular immunity and triggers tau hyperphosphorylation via GSK3β signaling. 177 …”
Section: The Role Of Gsk3 In Admentioning
confidence: 99%
“…It has also been reported that GSK3β affects the proportions of different isoforms of tau mRNA through alternative splicing. Prion protein PrPC serves as an upstream regulator that inhibits GSK3β activation 176 . Furthermore, interferon‐gamma (IFN‐γ) initiates cellular immunity and triggers tau hyperphosphorylation via GSK3β signaling 177 …”
Section: The Role Of Gsk3 In Admentioning
confidence: 99%